1991
DOI: 10.1128/iai.59.1.398-406.1991
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E release from human monocytes treated with lipopolysaccharides isolated from Bacteroides intermedius and Salmonella typhimurium: potentiation by gamma interferon

Abstract: The purpose of this investigation was to examine gamma interferon potentiation of lipopolysaccharide (LPS) responses in human monocytes by using phenol-water-extracted (unfractionated) and highly purified LPS preparations isolated from Bacteroides intermedius and Salmonella typhimurium. Phenol-water-extracted LPS preparations from these bacteria were further purified by chromatography over Sepharose-CL-4B. LPS enrichment in pooled column fractions was assessed by sodium dodecyl sulfate-polyacrylamide gel elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…4), some hydroxy fatty acids may also be constituents of lipopolysaccharide. Previous investigations have shown that the oral genera Bacteroides, Prevotella, and Porphyromonas incorporate 3-OH iC 17:0 into lipopolysaccharide (12,13,23,25,32), and lipopolysaccharide isolated from Bacteroides species can stimulate release of PGE 2 from monocytes (10,25). Lipopolysaccharide can facilitate attachment of organisms to epithelial surfaces (1,16,29) and can penetrate into the gingiva (30,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), some hydroxy fatty acids may also be constituents of lipopolysaccharide. Previous investigations have shown that the oral genera Bacteroides, Prevotella, and Porphyromonas incorporate 3-OH iC 17:0 into lipopolysaccharide (12,13,23,25,32), and lipopolysaccharide isolated from Bacteroides species can stimulate release of PGE 2 from monocytes (10,25). Lipopolysaccharide can facilitate attachment of organisms to epithelial surfaces (1,16,29) and can penetrate into the gingiva (30,33).…”
Section: Discussionmentioning
confidence: 99%
“…Among the beta-hydroxy fatty acids, 3-OH C 14:0 and 3-OH iso-branched C 17:0 (3-OH iC 17:0 ) are recovered in the gingival lipids, but a significant percentage of 3-OH C 14:0 is recovered in aqueous soluble components as well (23). Of these fatty acids, 3-OH iC 17:0 is synthesized by members of only four genera of oral microorganisms: Bacteroides, Capnocytophaga, Prevotella, and Porphyromonas (12,13,22,25,34); the remaining hydroxy fatty acids may be synthesized to a variable extent either by microorganisms or by the host. Therefore, recovery of 3-OH iC 17:0 in gingival lipids is presumed to represent penetration of specific bacterial lipids into the tissue.…”
mentioning
confidence: 99%
“…Frozen samples of oral strains of P. gingivalis obtained from gingivitis and periodontitis sites (generously provided by W. E. C. Moore) were also analyzed. Bacterial LPS isolates from P. intermedia and P. gingivalis were prepared as described previously (15). Bacterial samples and bacterial LPS isolates were analyzed for hydroxy fatty acid content as described below.…”
Section: Methodsmentioning
confidence: 99%
“…All derivatizing agents were obtained from Pierce Chemical Corp. (Rockford, IL, USA). The dried fatty acid samples were dissolved in acetonitrile (30 ml) and treated with 35% penta¯uorobenzyl bromide in acetonitrile (10 ml) and diisopropylethylamine (10 ml) (18). The solution was heated for 20 minutes at 40³C and evaporated to dryness under N 2 gas.…”
Section: Synthesis Of Fatty Acid Derivatives and Gc-ms Analysismentioning
confidence: 99%